Answer:
y = (6ln(x) + C)/x
A
is not a solution to the differential equation
x²y' + xy = x²
as required. This is probably due to an error in typing either the differential equation, or the value of y.
When you've checked the correct values, the same procedure is followed in obtaining the desired result.
Step-by-step explanation:
Suppose y = (6ln(x) + C)/x
is a solution to the differential equation
x²y' + xy = x²
Differentiate y with respect to x
y' = (6/x)/x - (6ln(x) + C)/x²
= (6 - 6ln(x) - C)/x²
Using this value in the differential equation,
x²(6 - 6ln(x) - C)/x² + x(6ln(x) + C)/x
= 6 - 6ln(x) - C + 6ln(x) + C
= 6